Divergence time analysis of the Neotropical wasp genus Protopolybia Ducke, 1905 (Vespidae, Polistinae, Epiponini) using a Multilocus Phylogenetic Approach - Junior, José N. A. Dos Santos; Silveira, Orlando T.; Carpenter, James M.; Cunha, Divino B. (Zootaxa, 2023)
The genus Protopolybia Ducke was analyzed using a multilocus phylogenetic approach, which confirmed its monophyly. In contrast with the arrangements derived solely from morphological data, however, this analysis divides the genus into only two major clades. The study also presents divergence times for the origin and diversification of Protopolybia, which are related to possible vicariant events occurring in the Amazon biome.